The Effect of NaOH Molarity and Nano Silica on Mechanical Properties of Ambient Cured PVA Fiber Reinforced Geopolymer Concrete - bin Abdul Hadi, Muhammad Zulkarnain (Universiti Teknologi PETRONAS, 2018)
As cement production contributes large scale of CO2 emissions, geopolymer concrete has been promoted as more environmental friendly material in construction industry. Hence, this report will discuss on the preliminary research on the effect of varied percentage of nano silica and NaOH molarity in ambient cured PVA fiber reinforced engineered geopolymer concrete in term of workability, setting time, compressive, flexural, and tensile strength. The results show that the addition of nano silica decrease the workability and setting time of fresh PVA reinforced geopolymer. The higher the NaOH molarity, the higher the compressive strength of samples regardless the presence of nano silica. Meanwhile, the nano silica give less significant impact on compressive strength, but eventually improve the flexural and tensile strength of samples.